An exploratory study of place-names in Sinai Peninsula, Egypt: a spatial approach. Issue 3 (3rd July 2018) - Zeini, Nahed T; Abdel-Hamid, Atef M; Soliman, Amal S; Okasha, Ahmed E
ABSTRACT: The Sinai Peninsula is a vital part of the Arab Republic of Egypt, geographically and historically. Its uniqueness and diversity of nature are reflected in its place-names, including both physical and human (cultural) features. The objectives of this study are to: (1) construct a digital geo-database of place-names; (2) classify the collected names based on their meanings to understand the motives behind naming them; and (3) utilize GIS-based spatial analysis techniques to map, geo-visualize and analyse the spatial distribution pattern of specific categories of such names. In this paper, the results show that most place-names are descriptive of the place they belong, either in whole or in part. They usually depict their geographical character and that in turn demonstrates how place-names and the naming process itself represent responses to the physical environment and cultural landscape and how place-names studies reveal patterns of settlement in the region under study.